Hubungan pola makan, mengonsumsi kopi dan tingkat stres dengan kejadian penyakit gastritis pada mahasiswa Coass Angkatan 2022 Fakultas Kedokteran Universitas Palangka Raya - Nugroho, Rendy Febry; Widodo, Tri; Shinta, Herlina Eka; Yuliani, Ni Nyoman Sri; Putra S, Ravenalla Abdurrahman Al Hakim Sampurna (Fakultas Kedokteran Universitas Palangka Raya, 2024)
Gastritis is inflammation of the mucosa and submucosa of the stomach, with symptoms of nausea, vomiting, bleeding, pain, reduced appetite which occurs in all ages from teenagers to old people. Gastritis can be caused by not paying attention to diet, drugs, alcohol, bacterial infections, drinking coffee, stress, illness and so on. This research is a quantitative research using a cross sectional design. Sampling used a simple random sampling technique. The estimated sample size was determined using the Lemeshow formula, namely 50 respondents. Statistical analysis used univariate analysis and bivariate analysis using the Fisher exact test and the Mann-Whitney test. The results of the bivariate analysis showed no relationship between diet and the incidence of gastritis (p-value=0.141), there was no relationship between consuming coffee and the incidence of gastritis (p-value=0.517) and there was no relationship between stress levels and the incidence of gastritis (p-value=0.237) in Coass students class of 2022, Faculty of Medicine, Palangka Raya University.